Cyberbullying: Causes of Online Harassment - Abd Rashid, Norasekin; Hairuddin, Hanitahaiza; Azani, Nurin Afiqah; Mohd Eza, Siti Nurbalqis; Engku Mohd Salleh, Engku Nur Hanisah Nadiah; Ayob, Nurazlina; Taupiang, Nur Aniah (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2025)
The use of social media has risen along with cyberbullying as the world gets more digitally linked. Based on a United Nations Children's Fund (UNICEF) report (2020), Malaysia is ranked as the second highest in Asia for cyberbullying among youth indicating that cyberbullying is becoming an increasingly prominent problem in the country. Research on cyberbullying has made significant progress in recent years, but understanding of cyberbullying behavior remains limited. Therefore, more investigation is needed to develop a comprehensive understanding of factors that influence cyberbullying behavior among adults in Malaysia. The current study aimed to examine the effect of anonymity, accessibility, and peer pressure on cyberbullying behavior among Malaysians. The quantitative research method is utilized by distributing the online questionnaire using Google Forms via face-to-face, email, and social networks. A total of 171 responses were collected and used for the data analysis. The findings show that anonymity, accessibility, and peer pressure have significant effects on cyberbullying behavior. In addition, the study also revealed that accessibility is the most influential factor in cyberbullying behavior. In the digital age, social media plays a central role and it is essential to foster a safe and respectful online environment. Additionally, addressing cyberbullying requires a collective effort from individuals, families, institutions, communities, and policymakers. Enforcing stricter laws and regulations to hold cyberbullies can serve as a deterrent and help to protect potential victims.